PENGEMBANGAN BĪ’AH LUGHAWIYYAH OLEH HIMPUNAN MAHASISWA JURUSAN PENDIDIKAN BAHASA ARAB DI IAIN PEKALONGAN - M Fairuz Rosyid (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2020)
This article aims to develop the bī'ah lughawiyyah carried out by the Student Association of the Arabic Language Education Institute of the State Islamic Institute of Pekalongan. This research focuses on the bī'ah lughawiyyah model in terms of the purpose of the bī'ah lughawiyyah, the forms of activities, and the learning model in the bī'ah lughawiyyah. This research method is qualitative, using interviews, observation, and documentation techniques. Data were analyzed using Miles and Huberman analysis. The perspective in this study is the theory of language environment proposed by Stephen D. Krashen. The results of this study indicate that the development model of bī'ah lughawiyyah based on "the purpose of learning about language," "learning languages" and "curricular objectives." The form of activities is in the way of learning module, nahwu sharaf study, bī'ah lughawiyyah, ilqā' mufradāt, Muhādatsah, Insya' monthly, language mading, rihlah lughawiyah, art and competition (PARBARA). There are three learning models, namely, student learning models with lecturers, student learning models with tutors and student and student learning models.